Adopting additive-hybrid manufacturing: the role of capacity in implementation decision. (2018) - Strong, Danielle; Kay, Michael; Wakefield, Thomas; Sirichakwal, Issariya; Conner, Brett; Manogharan, Guha
The integration of additive manufacturing (AM) with traditional manufacturing methods into 'hybrid manufacturing' has increased the potential uses of AM in the manufacturing industry. This paper explores the role of production resources in a traditional manufacturing facility and economic effects on the adoption of AM via hybrid manufacturing. A price competition model is used to analyse the effects of introducing hybrid manufacturing on the market structure of a standard product with regard to prices, quantities, and profits. Numerical results show that for products manufactured in a resource constrained environment, an adoption of hybrid manufacturing into one firm's portfolio, in addition to improving its own profitability, may potentially improve the profitability of its competitor who chooses not to adopt hybrid manufacturing. Firms can use this price competition model to determine whether they wish to be the 'first' in the market to offer hybrid-AM services or to compete with firms already offering such services.